Synthesis and Antitumor Evaluation of One Novel Tetramethylpyrazine-Rhein Derivative - Wang, Peng-Long; Cheng, Ya-Tao; Xu, Kuo; An, Ya-Wen; Wang, Wei; Li, Qu-Sheng; Han, Qiu-Jun; Li, Qiang; Zhang, Hong-Gui; Lei, Hai-Min (Asian Journal of Chemistry, 2013)
To discover multi-effective and low toxic anticancer lead compound from traditional Chinese medicine prescription, we synthesized one novel tetramethylpyrazine-rhein derivative which was composed of two main antitumor ingredients of Huazhenghuisheng Pian. The design idea was enlightened by "combination principle" in drug discovery and "compatibility principle" in traditional Chinese medicine. Compound 5's antitumor activity was evaluated by human cancer cell Bel-7402, while the angiogenesis activity was valued by the chick chorioallantoic membrane (CAM) assays. The stability test was carried on artificial gastric juice and artificial intestinal juice; furthermore, compound 5's acute toxicity was evaluated in vivo. The results showed that compound 5 not only displayed antiproliferative activity on Bel-7402 cell (IC50 = 26.4 μM), but also dramatically suppressed normal angiogenesis in chick chorioallantoic membrane. And there was no hydrolysis or structural damage during 24 h in artificial digestive solution. The LD50 value of the compound 5 exceeded 3.2 g/kg by oral administration in mice.